Speaking Across Cultures: Language Variation and Communication Patterns among Migrant Students in Higher Education - Salsa Putri Aprilia Hasan Azzahro; Nateta Dwi Desilva; Rafly Aurelian Alfattah Sutiyarto; Zam Zam Rafli Putra Handoko; Lucky Prasetyo Nggalene (KIRANA : Social Science Journal, 2026)
Linguistic and cultural diversity among university students creates complex communication dynamics, particularly for internal migrant students who must adapt to new social and linguistic environments. This study aimed to examine language variation among migrant students, identify the factors influencing language choice, and explore the relationship between language use and social adaptation at Universitas Pembangunan Nasional "Veteran" Jawa Timur. A descriptive quantitative approach was employed involving 20 first-year students selected through purposive sampling. Data were collected using an online questionnaire and analyzed through descriptive statistics, including frequency distributions and percentages. The findings revealed that Indonesian was the predominant language used in both academic and social interactions, including communication with classmates (80%), students from different regions (75%), and lecturers (100%). Although regional languages remained important as markers of cultural identity, their use on campus was relatively limited due to the need for more inclusive communication. Shared regional background emerged as the primary factor influencing language choice (52.6%), while differences in language and regional vocabulary represented the most significant communication barriers. Furthermore, appropriate language use was found to strengthen social relationships and facilitate students' social adaptation within a multicultural university environment. These findings highlight the importance of fostering intercultural communication practices to support inclusive and effective communication in higher education.